DeLisa's Physical medicine & rehabilitation : principles and practice - Frontera, Walter R., 1955-; DeLisa, Joel A. (Philadelphia : Lippincott Williams & Wilkins Health, 2010)
"DeLisa's Physical Medicine and Rehabilitation is the "gold standard" in the field of physical medicine and rehabilitation. It is the most modern and comprehensive book in the field. It can serve as both an introductory book for residents and a comprehensive reference book for practitioners. One volume covers physical medicine, the other rehabilitation medicine. Physical medicine covers principles of diagnosis and management, therapeutic approaches, and the management of specific conditions. Rehabilitation medicine covers the evaluation of the rehab patient, managing the rehab patient, and rehabilitation strategies and interventions"--Provided by publisher.
71.Therapeutic Electrical Stimulation in Neurorehabilitation / John Chae -- 72.Functional Neuromuscular Electrical Stimulation / John Chae -- 73.Assistive Technology / Cathy Bodine -- 74.Upper and Lower Extremity Prosthetics / Daniel Santa Maria -- 75.Upper Limb Orthotics / Heikki Uustal -- 76.Lower Extremity Orthotics, Shoes, and Gait Aids / Alberto Esquenazi -- 77.Spinal Orthotics / Eva Durand -- 78.Wheelchairs / Rosemarie Cooper -- 79.Complementary and Alternative Medicine / David Jung Seto -- pt. VII Scientific Advances -- 80.Evidence-Based Practice in Rehabilitation (Including Clinical Trials) / Alan M. Jette -- 81.Neural Repair and Plasticity / Steven C. Cramer -- 82.Regenerative Medicine: Implications in Rehabilitation / Fabrisia Ambrosio -- 83.Rehabilitation Robotics / N. Hogan.
ON ORDER
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Medical rehabilitation; Medicine, Physical; Physical Medicine -- methods; Rehabilitation; Electronic books